Complexometric Determination of Thallium(III) using Ethylene Thiourea as a Replacing Reagent. - JOSEPH, ABRAHAM; NARAYANA, B. (Asian Journal of Chemistry, 2010)
A simple and selective complexometric method is proposed for the determination of thallium(III). Thallium(III) with associated diverse metal ions, is first complexed by adding a known excess of EDTA and the surplus EDTA is back-titrated at pH 5.0–6.0(hexamine) with lead nitrate using xylenol orange as indicator. Ethylene thiourea solution (ETU in water)(1%) is added to displace EDTA from the Tl–EDTA complex. The released EDTA is then titrated with the lead nitrate solution. The interference of many commonly associated metal ions and diverse anions were also studied.